Correlation to predict conditions that lead to liquid-flooding at compressor start-up as a function of evaporator size and fluid properties. (February 2023) - Brendel, Leon P.M.; Pranatharthi Haran, Smrithi; Liu, Haotian; Braun, James E.; Groll, Eckhard A.
Highlights: Systematic investigation of liquid flooding upon compressor start-up. Characteristic flooding curve shown for 12 combinations of heat exchangers and refrigerants. Correlation proposed capturing influence of heat exchanger size and refrigerant properties. Abstract: Refrigeration cycles with fixed speed compressors cycle on and off to modulate their time averaged cooling capacity. While the cycles are turned off, refrigerant can migrate from the condenser into the colder evaporator. The next start-up process can then pull liquid refrigerant out of the evaporator and into the compressor causing liquid flooding. This phenomenon results in a loss of latent heat for cooling, can undercool the lubricant, and may cause damage to the compression mechanism. The geometric and thermophysical conditions that lead to liquid flooding are poorly understood. Experimental data collected for four refrigerants and three heat exchangers was analyzed for flooding conditions. A correlation was fitted to the experimental data, predicting the experimentally determined charge threshold for flooding with an average deviation of 6.6% and a maximum deviation of 16.7%. Repeating the tests with other heat exchanger types and smaller or larger compressors is suggested as important future work.